Risk experiments in gains and losses: A case study for Benin - Jonathan Gheyssens; Isabel Günther (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
The aim of this paper is to expand our knowledge on risk aversion among the poor by conducting experiments that do not only test risk aversion in small and large stakes but also in risky gains and risky losses. To our knowledge, this is the first attempt to conduct experiments in poor communities strictly focused on the loss domain. The experiments were conducted with 120 poor rural households in Benin. In contrast to results in industrialized countries, we find that playing lotteries constrained to the loss domain dramatically increases risk aversion. We also find a strong negative relationship between the level of risk aversion (both in gains and losses) and the level of religious faith. Our interpretation of this result is that villagers with strong beliefs tend to rely more on God's goodwill at the expense of a proper risk assessment, resulting in larger risk-taking.
Keywords: D81; O1; 330; risk aversion; loss aversion; religion; Landbevölkerung; Risikoaversion; Test; Benin